Delineation of an Octopus‐Like Thrombus Attached to the Eustachian Valve. Issue 4 (20th December 2013) - Kalcik, Macit; Toprak, Cüneyt; Ozan Gursoy, M.; Yesin, Mahmut; Ocal, Lutfi; Eren, Hayati; Özkan, Mehmet
<x xml:space="preserve">Abstract</x> Eustachian valve (EV) is a vestige of the valve of the inferior vena cava which directs the umbilical vein blood through open foramen ovale in fetal life. Following birth it gradually regresses, but it may persist in variable size, shape, and thickness as a functionless and benign structure. However, there are reports suggesting that persistent EV may not be completely innocent. It has been accused of being a predisposing cause of patent foramen ovale and paradoxical embolism and also interfering with transseptal interventional procedures. It may serve as a site of infective vegetations and be mistaken as a tumor or thrombus. In the present case, an octopus‐like thrombus attached to the EV was delineated with the utility of two‐dimensional and real time three‐dimensional transesophageal echocardiography. EV was considered to play an essential role in preventing potential pulmonary embolism.